2010
DOI: 10.1007/s12028-010-9437-z
|View full text |Cite
|
Sign up to set email alerts
|

Current Practices of Triple-H Prophylaxis and Therapy in Patients with Subarachnoid Hemorrhage

Abstract: There are substantial differences in the administration of prophylactic triple-H, but there was high agreement on indication for therapeutic use. There was wide variability in the extent of ICU monitoring, diagnostic approach, physiologic parameters and values used as target of therapy. NICU availability was associated with more intensive monitoring. Lack of evidence and guidelines for triple-H therapy might largely explain these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 16 publications
(11 reference statements)
1
49
0
1
Order By: Relevance
“…It is possible that the effect of norepinephrine on CBF is more predictable than the effect of dopamine. Phenylephrine is equally used as norepinephrine [49], without solid evidence for superiority of one agent over the other. AVP may be considered in patients who failed to respond to other vasopressor agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the effect of norepinephrine on CBF is more predictable than the effect of dopamine. Phenylephrine is equally used as norepinephrine [49], without solid evidence for superiority of one agent over the other. AVP may be considered in patients who failed to respond to other vasopressor agents.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent surveys of predominant strategies and practices for patients with aneurysmal subarachnoid hemorrhages have been published. One revealed that up to 60% of respondents used HHH therapy prophylactically (Sakowitz et al, 2006), whereas the second found that nearly 30% of respondents actively used the practice (Meyer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, it is practiced 30% to 60% of the time (Meyer et al, 2011;Sakowitz et al, 2006). Inducing hemodilution aims to maximize oxygen delivery across the stenosis of vasospastic vessels by decreasing viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of controlled comparative studies, the choice between PE and NE is often arbitrary and primarily dependent upon the preference of the treating clinician. A survey of Neurocritical Care Society members showed that 48% of providers primarily used PE, while 39% used NE [9]. However, theoretical and practical differences, which could be significant, exist.…”
Section: Introductionmentioning
confidence: 99%